The Impact of Artificial Intelligence (AI) and Social Media on Student Academic Performance: a Case Study at a Health College - Sirait, Noval Martahan Hasonangan; Bahri, Ronny Samsul (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study investigates the effects of Artificial Intelligence (AI), Smart Learning, and Social Media on academic performance among students at STIKES ARJUNA Laguboti, Toba, North Sumatra. Using a quantitative approach, data were collected from 225 students across three academic programs—Bachelor's in Pharmacy, Diploma in Pharmacy, and Diploma in Nursing—through random sampling. SmartPLS analysis reveals that Smart Learning and Social Media significantly enhance academic performance, with Smart Learning showing a strong positive impact, while Social Media fosters engagement and collaborative learning, indirectly improving outcomes. However, AI, while positively influencing Smart Learning, does not directly affect academic performance, suggesting that effective AI integration requires enhanced digital literacy and targeted interventions. These findings underscore the importance of integrating Smart Learning and Social Media into educational frameworks and addressing challenges in AI utilization to optimize academic success.